Factors affecting tumor response to transarterial chemoembolization (TACE) therapy in patient with hepatocellular carcinoma (HCC) - Alia Amalia; Nikmatia Latief; Bachtiar Murtala; Andi Alfian Zainuddin; Nu’man AS Daud (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Hepatocellular carcinoma (HCC) is a major problem of global health.Transarterial chemoembolization (TACE) is the treatment of choice for unresectable HCC. The TACE is routinely conducted in major hospitals in Indonesia, however it rarely published.The use of modified response in evaluation criteria in solid tumors (mRECIST) was introduced as an accurate method of measuring tumor response in HCC. This study aimedto investigate the factorsaffecting tumor response to TACE therapy in HCC patients by using mRECIST. It was a retrospective cohort study conducted on 30 patients who successfully underwent the first TACE procedure in the Department of Radiology, Dr. Wahidin Sudirohusodo General Hospital, Makassar, Indonesia from January 2016 to August 2019. The multiphase abdominal computed tomography before and after as well as laboratory examination results before TACE were collected and analyzed. Chi-Square and Spearman-tests were used for the statistical analysis. A significant relationship between tumor location (p=0.016), number of tumor (p=0.001) and Child-Pugh score with tumor response to TACE therapy (p = 0.016) was observed. Solitary tumors tend to have a better therapeutic response, meanwhile, tumors located in the left lobe of patients with Child-Pugh B scores showed a decreased tumor response. Furthermore, no a significant relationship between age (p=0.920), sex (p=0.303), tumor size> 5 cm (p=0.082) and alpha-fetoprotein (AFP) levels (p=0.414) with tumor response was observed. In conclusion, TACE is preferably therapy for multinodular and unresectable HCC. Tumor response after TACE can be well assessed using mRECIST. The factorsaffecting tumor response to TACE therapy arenumber of tumor, location, and Child-Pugh score